THE CONCEPT OF CONSTRUCTING A SYSTEM OF CONTROL AND REGULATION OF TRANSPORT SERVICES - B. P. Eliseev; A. S. Kamzolov (Научный вестник МГТУ ГА)
The article gives a brief analysis of the transport industry condition in the context of the provision of passenger transportation services, considers the existing problems of enterprises in the market economy conditions such as: the lack of guarantees and responsibility of suppliers to consumers, and vice versa (delays and non-payments, defaulters); forced lending to enterprises by transport companies and agencies, that means the use of banking services in the non-banking sector; the lack of developed for all types of transport domestic inventory and distribution systems based on the uniform requirements; the weakness of the existing system of control and prevention of dangerous trends, which leads to crises in the market and the chain reaction of insolvency of the participants. In this regard the article proves the justification for the creation of a unified system of control and regulation of transport services, aimed at providing control and monitoring of the conditions of the enterprises and the system as a whole, preventing dangerous trends and crises; providing mutual guarantees and protection of risks of both suppliers and consumers; creating a universal payment center; development of criteria for assessing market participants (ratings of solvency, reliability and other assessment methods). All this taken together will prevent negative consequences for transport companies. The structure of such a complex system, necessary subsystems and their functionality are considered. Specific solutions are proposed, whose implementation will allow constructing elements of a single control system on the basis of existing and operating in the industry inventory and distribution systems, as well as the mechanism of regulation and effective impact on the transport industry enterprises.